Drivers and constraints for adopting sustainability standards in small and medium-sized enterprises (SMEs) - Christoph Sommer (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Over the last decades, the continued internationalisation of production and the organisation of complex production networks into global value chains (GVCs) have fostered the relevance and spread of standards. While standards were initially concerned with the quality and compatibility of intermediaries, they have increasingly included an orientation to the production process. Social and environmental standards have the potential to foster sustainable supply chains and to empower small and medium-sized enterprises (SMEs) to integrate into GVCs and international markets. However, as many SMEs struggle to implement sustainability standards, emerging and developing countries raise concerns about discriminatory effects and standards as technical barriers to trade. This study examines the incentives and challenges that SMEs face in the adoption of sustainability standards, using evidence from five new country case studies from Brazil, China, India, Indonesia, and South Africa in triangulation with secondary data and existing literature in order to derive policy considerations. The key driver for standards implementation is demand for sustainably produced goods and services through GVCs and export markets, new domestic markets and public procurement. Yet implementation and certification costs impede the adoption of standards, as these (essentially) fixed costs weigh particularly heavy on smaller firms. Against this background, access to finance and the size and productivity of firms are also identified as two relevant constraints. Another important challenge is the lack of awareness among firms about sustainability standards, their relevance and their value to businesses. Most importantly, demand for sustainably produced goods and services has to be raised through the appropriate public procurement strategies and through promotion of SME integration into sustainable GVCs. Mutually beneficial cost-sharing schemes with lead firms and the development of multi-stage certification processes by standard setters that verify and reward first steps in transition to full compliance, could mitigate the problem of implementation and certification costs. Information platforms such as national voluntary sustainability platforms under the auspices of the United Nations Forum on Sustainability Standards (UNFSS) can bridge the information gap for SMEs. It is also crucial to involve financial institutions: development finance institutions should take a leading role and embed standards compliance into the terms and conditions of lending contracts, while central bank requirements could strengthen sustainability criteria in the credit assessment among commercial banks.
Keywords: 320; Governance; Handel und Investitionen